The use of Indole Butyric Acid on the growth of dragon fruit plant stem cuttings - SISWA PANJANG HERNOSA; SANGGAM DERA ROSA TAMPUBOLON; LUTHFI AZIZ MAHMUD SIREGAR (Nusantara Bioscience, 2022)
Abstract. Hernosa SP, Tampubolon SDR, Siregar LAM. 2022. The use of Indole Butyric Acid on the growth of dragon fruit plant stem cuttings. Nusantara Bioscience 14: 211-216. The difficulty of root growth of dragon fruit cuttings is affected by stem rot; one way to increase the growth of cuttings is to use a growth regulator, namely Indole Butyric Acid (IBA), which is used to stimulate the growth of dragon fruit rootstock cuttings. This research was conducted in Sidorukun Village, Pangkatan Sub-district, Labuhan Batu District, North Sumatra, Indonesia, at an altitude of ± 40 m above sea level, from June to October 2020. The research design used was a randomized block design with five treatments. The concentration of the IBA hormone consists of B0 : 0 ppm, B1: 4,500 ppm, B2: 5,500 ppm, B3: 6,500 ppm, B4: 7,500 ppm, and five replicates, so the entire experimental plot was 25. Parameters observed were percentage of shoot emergence, age of shoot emergence, shoot length (cm), shoot fresh weight (g), shoot dry weight (g), root length (cm), fresh root weight (g), root volume (g), and root dry weight (g). Data analysis used a linear model followed by Duncan's test. It is known that the administration of Indole butyric acid (IBA) significantly affected the observed parameters on shoot emergence, age of shoot emergence, number of shoots, root length, fresh root weight, root volume, and root dry weight. However, it did not affect the observed parameters, namely, shoot length, shoot fresh weight and shoot dry weight. On the other hand, B4 concentration (7,500 ppm) gave better shoot growth, root weight, and root dry weight.